CT-guided fine-needle aspiration of abdominal and retroperitoneal small lesions with the coaxial technique using MPR images - De Filippo, Massimo; Saba, Luca; Azzali, Emanuele; Milanese, Gianluca; Mostardi, Maurizio; Borgia, Daniele; Capasso, Raffaella; Nizzoli, Rita (Acta Biomedica Atenei Parmensis, 2016)
Purpose: To demonstrate the advantages of CT-guided fine-needle aspiration (FNA) of abdominal and retroperitoneal small lesions with the coaxial technique using MPR images. Materials and methods: The study included retrospectively 50 patients who underwent CT-guided FNA of abdominal and/or retroperitoneal small lesion (